Measuring the financial efficiency of PPP toll road projects in the Republic of Korea - BYUN, Hyeri (KDI School, 2018)
Analysis has been performed to document success and failure factors of the Public-Private Partnership (PPP) market in Korea to assist in establishing effective PPP policy. Since it is difficult to define success or failure based on one dependent variable or output, and to make identification of objective relationships between multiple inputs and outputs possible, Data Envelopment Analysis (DEA) has been used to measure the success of PPP road projects in Korea. The most significant difference setting this work apart from other papers using DEA is a focus on the financial aspects of PPP projects instead of the governmental perspective, viewing PPP projects as a type of Project Financing (PF) investment. In this study, an input-oriented Banker, Chames and Cooper (BCC) model was used for analysis, and the input and output factors for DEA were as follows: input factors included operating cost, Amortization of Management and Operation Rights (AMOR), and interest expense, while output factors consisted of Cash Flow from Operating Activities (CFOA), traffic volume (annual average daily traffic), and sales. Overall findings show that projects with a high efficiency score are characterized by a medium input level with a high level of output, and projects in the Seoul metropolitan area or those receiving a higher ratio of MRG to sales tended to receive higher efficiency scores. Policy implications are as follows: The government needs to estimate traffic volume more carefully and thoroughly, especially when proceeding with new projects in local areas or non-Seoul metropolitan areas through the use of a periodical monitoring system for demand while also tightening up internal supervision over the authority in charge. Also, the government would do well to make a continuous effort to reduce the fiscal burden by altering the subsidy payment mechanism from MRG to MCC.
Thesis(Master) --KDI School:Master of Public Policy,2018